Distributed generation allocation to reduce losses and improve voltage profile genetic algorithm: article - Abdol Azis, Hazriq Syahmie (2010)
This paper presents a method for the optimal allocation of Distributed generation in distribution systems. In this paper, the aim would be optimal distributed generation allocation for voltage profile improvement and loss reduction in distribution network. Genetic Algorithm (GA) was used as the solving tool, which referring two determined aim the problem is defined and objective function is introduced. Considering to fitness values sensitivity in genetic algorithm process, there is needed to apply load flow for decision-making. Lead flow algorithm is combined appropriately with GA, till access to acceptable results of this operation. I used Newton Raphson for load flow algorithm and composed it with Genetic Algorithm. The suggested method is programmed under MATLAB software. The resulting operation of this method on some testing system is illuminated improvement of voltage profile and loss reduction indexes.